Techniques for Future Enhancement for Security of Cloud Computing - Sagotra, Diksha; Kaur, Harjinder (International Journal of Computer Sciences and Engineering, 2021)
In cloud computing data and applications have been maintained using remote servers that is distributed and it utilizes internet. The main advantage of using cloud computing is that it allow user to use applications over the internet and also share files at any computer over the internet. The use of cloud computing has tremendous impact over the IT industry and also it provides efficient use of resources like bandwidth, storage and processing. As the growth of cloud computing increases many users interact with each other and security issues are arising. The cloud computing growth is hampered by these security issues. There are risks of data breach, data loss, unauthorized access, denial of services etc. In this paper the analysis cloud computing security issues and also surveyed various techniques that are used to handle cloud security.